The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.lfs.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of exercise on the heart

Abstract: Pathologic and physiologic factors acting on the heart can produce consistent pressure changes, volume overload, or increased cardiac output. These changes may then lead to cardiac remodeling, ultimately resulting in cardiac hypertrophy. Exercise can also induce hypertrophy, primarily physiologic in nature. To determine the mechanisms responsible for each type of remodeling, it is important to examine the heart at the functional unit, the cardiomyocyte. Tests of individual cardiomyocyte function in vitro provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
3
0
2
Order By: Relevance
“…When moderate exercise is practiced regularly, it can decrease the chances of dying from cardiovascular disease by the reduction of risk factors such as hypertension, obesity and hyperlipidemia, and physical activity; it also enhances longevity by mechanisms independent of these risk factors [15,16]. In addition, there are results demonstrating that moderate physical exercise plays a key role on reducing the risk of cardiovascular diseases in elderly subjects [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…When moderate exercise is practiced regularly, it can decrease the chances of dying from cardiovascular disease by the reduction of risk factors such as hypertension, obesity and hyperlipidemia, and physical activity; it also enhances longevity by mechanisms independent of these risk factors [15,16]. In addition, there are results demonstrating that moderate physical exercise plays a key role on reducing the risk of cardiovascular diseases in elderly subjects [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Při tlakovém přetížení se vyvine koncentrická hypertrofi e, kardiomyocyty se individuálně rozšiřují zapojením nových sarkomer paralelně a tloušťka srdeční stěny se zvětší. 2,7 Pro zachování funkce komor při tlakovém přetížení není ovšem hypertrofi e vždy potřeba. Za určitých podmínek může představovat adaptivní i maladaptivní typ remodelace.…”
Section: Hypertrofi Eunclassified
“…Většina sportovních aktivit kombinuje izotonický a izometrický druh svalové práce. 7,18,19 Pojem atletické srdce zahrnuje soubor remodelačních změn vzniklých v reakci na dlouhodobou opakovanou intenzivní fyzickou zátěž. Významný rozvoj atletického srdce byl popsán u osob věnujících se vytrvalostním sportům.…”
Section: Atletické Srdceunclassified
“…Initially, the increasing expression of myocardial peroxisome proliferator-activated receptor (PPARα) was detected during treadmill training in mice ( Dobrzyn et al., 2013 ). Later, it was found that the level of PPARα also increased in exercise-induced physiologic hypertrophic cardiomyocytes ( Youtz et al., 2014 ). In addition, some experiments found that gene expression of PPARα was reduced in pathological cardiac hypertrophy, suggesting that upregulation of PPAR-α expression may limit pathological cardiac hypertrophy ( Barger et al., 2000 ).…”
Section: The Signaling Molecules Of Metabolism In Exercise-induced Phmentioning
confidence: 99%